Massive obstetric haemorrhage on post caesarean subtotal hysterectomy due to late detection of occult placenta percreta: A case report. (August 2021) - Purwoto, Gatot; Surya, Ilham Utama; Saroyo, Yudianto Budi; Rustamadji, Primariadewi; Harzif, Achmad Kemal
Abstract: Introduction: Placenta accreta syndrome is a significant cause of maternal mortality and morbidity. Therefore, a multidiscipline approach is essential to overcome this life-threatening disorder for the mother and fetus. Presentation of case: A 32-year-old women gravida 3 parity 2, 34 weeks gestation come due to recurrent antepartum haemorrhage. She had twice prior caesarean section. Ultrasound assessment suggests total placenta previa and elevating suspicion to placenta accreta. However, intraoperatively its sign is unavailable. Although we have done subtotal hysterectomy, massive bleeding still occurring. Therefore, we present management of unexpected placenta percreta. Discussion: Management of unexpected placenta percreta involves prenatal diagnosis, haemoglobin optimization, surgical management anticipating haemorrhage, dedicated maternal ICU, blood bank providing massive transfusion and blood component. Conclusion: Close monitoring is important in catastrophe management of Placenta Accreta Syndrome. Highlights: Placenta accreta spectrum should be considered from risk factor, prenatal diagnosis and intraoperative findings. Not only to bladder and colon, but placenta percreta can invade vagina. The standard treatment for placenta percreta is total hysterectomy. The multi-discipline approach is important in managing placenta accrete syndrome.